2007
DOI: 10.1111/j.1365-2109.2007.01674.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of genetic strain and holding facility on the characteristics of alkaline phosphatase and brush border enzymes in silver perch (Bidyanus bidyanus)

Abstract: The activity of the enzymes located in the digestive tract (pyloric caeca and intestine) in two strains and F1 crosses of the Australian freshwater fish silver perch [Murray River (M) and Cataract Dam (C)] was evaluated. The effect of the fish holding system (cages or ponds) on the activity of alkaline phosphatase (AP) and the brush border enzymes: maltase, leucine amino peptidase (LAP) and γ‐glutamyl transferase (γ‐GT) was examined. The enzymatic activity was tested in three intestinal sections: the pyloric c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 35 publications
1
10
0
Order By: Relevance
“…Similar results have been reported for other species such as S. maximus (Cousin et al 1987) and D. labrax (Cahu and Zambonino-Infante 1997). The pattern of activity coincided with that of other brushborder enzymes which should indicate a maturation of enterocytes (Zambonino-Infante and Cahu 2001; Hakim et al 2007), while the clear drop in all activity from 12 dah onwards may be related to the onset of stomach activity.…”
Section: Days After Hatching (Dah) Embryomentioning
confidence: 76%
“…Similar results have been reported for other species such as S. maximus (Cousin et al 1987) and D. labrax (Cahu and Zambonino-Infante 1997). The pattern of activity coincided with that of other brushborder enzymes which should indicate a maturation of enterocytes (Zambonino-Infante and Cahu 2001; Hakim et al 2007), while the clear drop in all activity from 12 dah onwards may be related to the onset of stomach activity.…”
Section: Days After Hatching (Dah) Embryomentioning
confidence: 76%
“…Likewise in the present study also, four gobiid species (G. giuris, T. buchanani, P. novemradiatus and T. vagina) were found in proximity in the dendrogram when overall digestive enzyme patterns were considered. Influence of the genetic traits on the activities of brush border enzymes was demonstrated in the crosses of Oreochromis mossambicus (Peters, 1852) and O. aureus (Steindacher, 1864) (Hakim et al 2006) and in the silver perch Bidyanus bidyanus (Mitchell, 1838) (Hakim et al 2007). Furthermore, the activities of digestive enzymes were also influenced by many other factors such as the ages of the fishes (Kuźmina 1996), temperature and season and the composition of their diets (Zambonino-Infante and Cahu 2001).…”
Section: Discussionmentioning
confidence: 97%
“…Their results showed that the activities of digestive enzymes correlated more strongly with phylogeny rather than with the fish's natural diets. Influence of the genetic strains on the activities of brush border enzymes was demonstrated in the crosses of Oreochromis mossambicus and O. aureus (Hakim et al, 2006) and in the silver perch Bidyanus bidyanus (Hakim et al, 2007). Furthermore, the activities of digestive enzymes were also influenced by many other factors such as the ages of the fishes (Kuźmina, 1996), temperature and season (Kuźmina et al, 1996b) and the composition of their diets (Zambonino Infante and Cahu, 2001).…”
Section: Discussionmentioning
confidence: 97%